The Impact of the Paris Agreement on the Right to Clean Air in Indonesia - Mansora Pooya (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2026)
Global warming is not only an environmental issue but also a human rights issue, especially in relation to the right to clean air. The paper critically examines the application of the Paris Agreement to the Indonesian scenario and the implications of the agreement on air quality and the health of people. The current analysis presents a normative approach to legal research, where the policies, regulations, and Nationally Determined Contributions (NDCs) of countries are reviewed through the prism of international climate commitments. The empirical findings state that despite the positive changes in regulatory frameworks, there are still obstacles to the successful protection of clean air, such as coal dependence, inadequate enforcement systems, forest fires, etc. Policy recommendations emphasize the need for a shift towards renewable energy, the implementation of stricter regulatory processes, and the incorporation of human rights considerations.